CowParade Houston : The Cows, The Artists - Over 320 Moovers and Shakers - CowParade New York (2000); Craughwell, Thomas J., 1956-; CowParade Holdings Corporation (New York : Workman Pub., 2000)
Takes readers on a tour of New York City with the fiberglass cows of the summer 2000 "CowParade" exhibit, presenting historical information on each section of the city, profiles of several Cowparade artists, and hundreds of color photos of the bovine artworks.
120.
Keywords: Cows in art -- Exhibitions; Public sculpture -- New York (State); New York; Exhibitions; Community arts projects -- New York (State); New York; Exhibitions; Cows -- Anecdotes; Sculpture